Comparative Genome Analysis of Hungarian and Global Strains of Salmonella Infantis - Nagy, Tibor; Szmolka, Ama; Wilk, Tímea; Kiss, János; Szabó, Mónika; Pászti, Judit; Nagy, Béla; Olasz, Ferenc (Frontiers in Microbiology, 2020)
ABSTRACT Introduction: The emergence and spread of new strains of zoonotic bacteria, such as multidrug resistant Salmonella Infantis, represent a growing health risk for humans due to foodborne infections of poultry meat origin. Objectives: In order to understand genome relations of S. Infantis strains from Hungary and from different geographic regions, we performed a comprehensive genome analysis of 9 Hungarian and 39 globally selected strains of S. Infantis and 26 Salmonella strains representing 13 non-Infantis serovars. Results: Analyses of whole-, and accessory genomes, as well as of genomic islands showed that almost all S. Infantis strains formed a single clade and were clearly separated from the non-Infantis serovars. S. Infantis strains from Hungary formed two distinct subclusters based on their time of isolation. The Swiss strains of S. Infantis were closely related to each other and clustered together with several strains from Italy, Israel, Japan, and Peru, and were unambiguously distinct from the Hungarian subclusters. Genomic sequences of six strains from Brazil, Mexico and Senegal deposited as S. Infantis proved to be outliers from the S. Infantis clade. They were predicted to be S. Rissen, S. Ouakarm and S. enterica subsp. diarizonae indicating that these outliers of S. Infantis need re-classification. Conclusion: We suggest that establishment of possible epidemiologic links between strains from different countries needs a comprehensive and harmonized analysis of several genomic characteristics. The core genome analysis provided the least discriminatory power while analysis of the cloud genes and genomic islands offered the most detailed insight into the genetic distance and relationship of S. Infantis strains. Accessory genome of S. Infantis showed the highest diversity suggesting a faster evolution of the islands than that of the whole genomes thereby contributing to the emergence of multiple genetic variants of S. Infantis worldwide.